2017
DOI: 10.1080/10641963.2016.1235183
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure control with cilnidipine treatment in Japanese post-stroke hypertensive patients: The CA-ATTEND study

Abstract: Blood pressure control is important in post-stroke hypertensive patients and antihypertensive treatment is recommended for such patients. Ca-channel blockers are recommended as the medications of choice for the treatment of post-stroke patients. Here, we report the results of a large-scale prospective postmarketing surveillance study of post-stroke hypertensive patients (n = 2667, male 60.4%, 69.0 ± 10.9 years) treated with cilnidipine, with regard to blood pressure control and adverse reactions. Cilnidipine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Dizziness and decrease in blood pressure were not serious ADRs and were resolved or resolving in all patients. (between May 2011 and June 2013) (20). We have also reported that the incidence rate of adverse reactions due to coadministration of cilnidipine and ARBs was 2.50% (73 of 2920 patients) (From February 2003 to July 2004) (15), and the incidence rate in the selected 615 patients who were administered 10 mg cilnidipine and 80 mg valsartan was 3.25% (20 of 615 patents) (21).…”
Section: Discussionmentioning
confidence: 93%
“…Dizziness and decrease in blood pressure were not serious ADRs and were resolved or resolving in all patients. (between May 2011 and June 2013) (20). We have also reported that the incidence rate of adverse reactions due to coadministration of cilnidipine and ARBs was 2.50% (73 of 2920 patients) (From February 2003 to July 2004) (15), and the incidence rate in the selected 615 patients who were administered 10 mg cilnidipine and 80 mg valsartan was 3.25% (20 of 615 patents) (21).…”
Section: Discussionmentioning
confidence: 93%
“…The study design, patient characteristics, and main BP results of the CA-ATTEND study have been reported elsewhere 15 ) . This study was registered in the University Hospital Medical Information Network Clinical Trials Registry (UMIN000005523).…”
Section: Methodsmentioning
confidence: 99%
“…The Carotid Atherosclerosis-Antihypertensive Treatment Trial, Effect of N-type Calcium Channel Blocker for Cerebrovascular Disease (CA-ATTEND) study is a 12-month, large-scale ( n = 2,667), prospective postmarketing surveillance (PMS) study in which the efficacy and safety of cilnidipine were investigated in registered post-stroke hypertensive patients on the basis of pressure (BP) and atherosclerosis of the common carotid arteries 15 ) . Cilnidipine is a dual L/N-Type calcium channel blocker that can block not only L-type vascular calcium channels but also N-type calcium channels in the sympathetic nerves 16 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In another large-scale prospective post-marketing surveillance study of post-stroke hypertensive patients (n = 2667, male 60.4%, 69.0 ± 10.9 years) who were treated with Cilnidipine, the blood pressure control with Cilnidipine treatment was very good [ 14 ].…”
Section: Introductionmentioning
confidence: 99%